2003
DOI: 10.1016/s1074-7613(03)00111-0
|View full text |Cite
|
Sign up to set email alerts
|

Notch2 Is Preferentially Expressed in Mature B Cells and Indispensable for Marginal Zone B Lineage Development

Abstract: The Notch genes play a key role in cellular differentiation. The significance of Notch1 during thymocyte development is well characterized, but the function of Notch2 is poorly understood. Here we demonstrate that Notch2 but no other Notch family member is preferentially expressed in mature B cells and that conditionally targeted deletion of Notch2 results in the defect of marginal zone B (MZB) cells and their presumed precursors, CD1d(hi) fraction of type 2 transitional B cells. Among Notch target genes, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
534
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(575 citation statements)
references
References 47 publications
36
534
1
4
Order By: Relevance
“…29,30 Furthermore, in support of this notion, we confirmed by real-time PCR analysis that endogenous RBP-J level in NotchIC transgenic mice did not significantly change as compared to that in control mice, but endogenous Deltex1 level increased significantly (Supplementary Figure 1). 22 Recently, it was also shown that RBP-J-mediated Notch signaling is dispensable for the lineage commitment, survival, and maturation of CD4/CD8 T-cells. 23 In addition, retroviral expression of Deltex1 alone in primary thymocytes and 16610D9 cells was sufficient for the acquisition of resistance to GCs (Figure 6b and c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 Furthermore, in support of this notion, we confirmed by real-time PCR analysis that endogenous RBP-J level in NotchIC transgenic mice did not significantly change as compared to that in control mice, but endogenous Deltex1 level increased significantly (Supplementary Figure 1). 22 Recently, it was also shown that RBP-J-mediated Notch signaling is dispensable for the lineage commitment, survival, and maturation of CD4/CD8 T-cells. 23 In addition, retroviral expression of Deltex1 alone in primary thymocytes and 16610D9 cells was sufficient for the acquisition of resistance to GCs (Figure 6b and c).…”
Section: Discussionmentioning
confidence: 99%
“…10 However, since Deltex1 interacts with the first three ankyrin repeats of NotchIC, 21 the possibility that the downstream effects of the Notch signaling may also be mediated by the Deltex1-dependent mechanism cannot be completely excluded. Furthermore, the level of RBP-J expression is not significantly changed during thymocyte differentiation from double negative (DN) to DP and from DP to SP stages, 22 whereas Deltex1 is expressed at a relatively high level in CD4 and CD8 SP thymocytes and at a low level in DP thymocytes. 20,22 Recently, it has been reported that RBP-J deficiency does not significantly perturb the development of DP thymocytes into CD4 and CD8 SP lineages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jagged1‐floxed knockin mice ( Jagged1 lox/lox )12 were crossed with Mx‐Cre transgenic mice13 to generate polyinosinic‐polycytidylic acid [poly(I):poly(C)]‐inducible Jagged1 cKO mice. Notch2 ‐floxed knockin mice ( Notch2 lox/lox )14 were mated with Albumin‐Cre transgenic mice15 [C57BL/6TgN(AlbCre)21Mgn strain from Jackson Laboratory, Bar Harbor, ME] to achieve hepatocyte‐specific Notch2 gene deletion. Both strains of mice were back‐crossed with C57BL/6 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of the Notch1 receptor perturbs T-cell development, yet the B-cell compartment appears unaffected (Radtke et al, 1999). Conversely, the targeted inactivation of the Notch2 receptor or Dll1 ligand results in a loss of marginal zone B cells (MZB cells), but T-cell development appears normal (Saito et al, 2003;Hozumi et al, 2004). Importantly, these effects are consistent with phenotypes caused by the inactivation of canonical Notch signaling in these compartments, because loss of the transcription factor CSL blocks both T-cell development and MZB cell generation Tanigaki et al, 2002).…”
Section: Identification Of Maml Proteins and Investigations Into Theimentioning
confidence: 99%